(untitled) (Research, Society and Development, 2022)
Lactose Intolerance (IL) is a very common morbidity and is distinguished as the difficulty or inability of the body to absorb lactose due to the deficiency or lack of the lactase enzyme in the body. Lactose Intolerance is divided into three main types, congenital, primary or adult type and secondary or acquired; when IL develops in the body it usually has symptoms such as flatulence, diarrhea and vomiting, which are the most recurrent and common symptoms. In order to obtain more data about lactose intolerance commonly developed in adulthood, a field survey was carried out using an electronic questionnaire on the Google Forms platform as a methodology, in which it pointed out that most of the people who were available to answer the questionnaire are female and people most affected by this disease are aged from 25 years.